Fate-tracking early coral recruits following bleaching in a remote reef ecosystem - Stratford, John E.; Mogg, Andrew O. M.; Koldewey, Heather J.; Lachs, Liam; Ferrari, Renata; Guest, James; Bayley, Daniel T. I. (Coral reefs, 2025)
As coral reefs face increasingly frequent and severe disturbances, their condition relies more heavily on recovery dynamics. Understanding reef recovery is essential for assessing the long-term ecological integrity and functioning of these ecosystems. In this study, we used structure-from-motion photogrammetry to map reefs at Peros Banhos atoll (Chagos Archipelago) in the three years following the 2015–2016 mass coral bleaching event. This approach enabled us to detect and track individual post-bleaching coral recruits underpinning natural recovery ( n = 1,074 across 72 m 2 ), and investigate their early survival and growth. In 2017, one year after the bleaching, new recruit density was highest, largely due to comparatively high recruitment in sheltered sites. However, 2018 recruits had higher first-year survival and growth than the 2017 cohort, suggesting a negative legacy effect of high temperatures on reef recovery. Branching coral taxa showed both the highest first-year survival and growth. Interestingly, fine-scale substrate complexity at the onset of recovery was negatively associated with the density of recruits 1–2 years later. Despite favourable conditions that allowed the majority of recruits to survive and grow rapidly, all recruits combined accounted for only 2.39% coral cover three years after the bleaching event. Our results document vital rates during early natural recovery at a remote protected atoll and shed light on the dynamics of coral recruits immediately following mass bleaching. Further, we demonstrate the insight that photogrammetric approaches can provide to reef demographic studies.